2022
DOI: 10.1126/sciadv.abl6989
|View full text |Cite
|
Sign up to set email alerts
|

Trips and neurotransmitters: Discovering principled patterns across 6850 hallucinogenic experiences

Abstract: Psychedelics probably alter states of consciousness by disrupting how the higher association cortex governs bottom-up sensory signals. Individual hallucinogenic drugs are usually studied in participants in controlled laboratory settings. Here, we have explored word usage in 6850 free-form testimonials about 27 drugs through the prism of 40 neurotransmitter receptor subtypes, which were then mapped to three-dimensional coordinates in the brain via their gene transcription levels from invasive tissue probes. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 63 publications
(96 reference statements)
2
49
0
1
Order By: Relevance
“…The eleven significant components reveal latent patterns of correlation between drug receptor affinity and word-usage from subjective testimonials. Each is traced to specific cortical sites using receptor RNA expression as measured by invasive tissue probes, building on prior research (4) by incorporating more substances and testimonials. For example, the dominant component, CCA 0, lucid-beauty and CCA 2, cosmic-expansion, localized gene expression for canonical hallucinogenic 5-HT2A and KOR receptors (27) to high-level integration hubs like the medial prefrontal cortex, dorsal anterior cingulate cortices, and temporoparietal junction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The eleven significant components reveal latent patterns of correlation between drug receptor affinity and word-usage from subjective testimonials. Each is traced to specific cortical sites using receptor RNA expression as measured by invasive tissue probes, building on prior research (4) by incorporating more substances and testimonials. For example, the dominant component, CCA 0, lucid-beauty and CCA 2, cosmic-expansion, localized gene expression for canonical hallucinogenic 5-HT2A and KOR receptors (27) to high-level integration hubs like the medial prefrontal cortex, dorsal anterior cingulate cortices, and temporoparietal junction.…”
Section: Resultsmentioning
confidence: 99%
“…The CCA mapping between testimonials and affinities is described in detail in the Trips and Neurotransmitters paper (4). The approach here only differs in the size and provenance of the data used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last year, human neuroimaging studies identified the involvement of the dopaminergic system in both propofol-induced anaesthesia 51 and the subjective effects of LSD 52 . More broadly, a recent large-scale study, combining receptor expression from transcriptomic data with linguistic processing of several thousand subjective reports of psychedelic use, identified complex multivariate patterns of association between neurotransmitters and their effects on the mind elicited by a wide variety of psychedelics, even for putatively selective agents 53 . At the same time, molecularly different compounds can exert intriguingly similar effects on both the mind and brain: for instance, LSD and (sub-anaesthetic) ketamine can produce subjectively similar effects and changes in terms of structure-function coupling and the complexity of brain activity - despite acting on different pathways 21 .…”
Section: Introductionmentioning
confidence: 99%
“…This is complicated by the highly individualistic and subjective nature of the perceptual experiences, as well as variability in drug potency and purity. Precision medicine requires a novel approach, and a Science Advances article 3 does just that, using linguistic analysis of reported drug experiences and linking these via drug affinity to known receptor effects and locations to create a three-dimensional map of specific types of hallucinogenic experiences in the brain. Nearly 7000 first-person narratives of drug-induced experiences from the Erowid Center's Experience Vault () were used.…”
mentioning
confidence: 99%